A Histologic and Histomorphometric Analysis of Bone Tissue Regeneration with Perforated Bone Allograft in Rabbit Femur Defect - Tuleubaev, B. E.; Kamyshansky, E. K.; Saginova, Saginova Dina; Tashmetov, E. R.; Koshanova, A. A. (Open Access Macedonian Journal of Medical Sciences, 2021)
AIM: The aim of this study is to provide a comparative histopathological evaluation of the regeneration of bone defect filling with perforated antibiotic-impregnated bone allograft. MATERIALS AND METHODS: Seventy-two healthy rabbits (24 rabbits in each group) were used for this study. Bone defects (3-mm diameter, 10-mm depth) were created in the femur. Human femoral head prepared according to the Marburg bone bank system was used as a bone allograft. The control group did not receive any filling. The experimental groups were as follows: Group 1 – the defects were filled with bone allografts and Group 2 – Perforated gentamycin-impregnated bone allografts. The animals were euthanized after 14, 30, and 60 days. Evaluations consisted of histology at 14-, 30-, and 60-days post-surgery. RESULTS: A mature bone formation in the group without a bone allograft occurred after 30 days and the group with an allograft after 14 days. In the groups with an allograft, a bone marrow defect was noted as complete closure after 30 days. Histomorphometric analysis showed that in the group with an antibiotic-impregnated bone, allograft leads to increased resorption of the allograft in the intramedullary space compared to group without antibiotic. CONCLUSION: We believe that a perforated allograft as a result of clinical trials may be obvious and economically affordable in the treatment of bone defects. The use of gentamycin-impregnated bone allografts may be of value in the prevention and treatment of bone infections.